Photochemical and Nonphotochemical Fluorescence Quenching Processes in the Diatom Phaeodactylum tricornutum. - Ting, C. S. (1993)
Nonphotochemical fluorescence quenching was found to exist in the dark-adapted state in the diatom Phaeodactylum tricornutum. Pretreatment of cells with the uncoupler carbonylcyanide m-chlorophenylhydrazone (CCCP) or with nigericin resulted in increases in dark-adapted minimum and maximum fluorescence yields. This suggests that a pH gradient exists across the thylakoid membrane in the dark, which serves to quench fluorescence levels nonphotochemically. The physiological processes involved in establishing this proton gradient were sensitive to anaerobiosis and antimycin A. Based on these results, it is likely that this energization of the thylakoid membrane is due in part to chlororespiration, which involves oxygen-dependent electron flow through the plastoquinone pool. Chlororespiration has been shown previously to occur in diatoms. In addition, we observed that cells treated with 3-(3,4-dichlorophenyl)-1,1-dimethylurea exhibited very strong nonphotochemical quenching when illuminated with actinic light. The rate and extent of this quenching were light-intensity dependent. This quenching was reversed upon addition of CCCP or nigericin and was thus due primarily to the establishment of a pH gradient across the thylakoid membrane. Preincubation of cells with CCCP or nigericin or antimycin A completely abolished this quenching. Cyclic electron transport processes around photosystem I may be involved in establishing this proton gradient across the thylakoid membrane under conditions where linear electron transport is inhibited. At steady state under normal physiological conditions, the qualitative changes in photochemical and nonphotochemical fluorescence quenching at increasing photon flux densities were similar to those in higher plants. However, important quantitative differences existed at limiting and saturating intensities. Dissimilarities in the factors that regulate fluorescence quenching mechanisms in these organisms may account for these differences.